1996
DOI: 10.1073/pnas.93.20.11253
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of pressure-activated Ca(2+)-permeable cation channel in intact vascular endothelium of hypertensive rats.

Abstract: In endothelial cells, stretch-activated cation channels have been proposed to act as mechanosensors for changes in hemodynamic forces. We have identified a novel mechanosensitive pressure-activated channel in intact endothelium from rat aorta and mesenteric artery. The 18-pS cation channel responded with a multifold increase in channel activity when positive pressure was applied to the luminal cell surface with the patch pipette and inactivated at negative pipette pressure. Channel permeability ratio for K+, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
1
24
1
Order By: Relevance
“…In endothelial cells, a pressure increase can stimulate stretch-activated cation channels and induce Ca 2ϩ influx that induces endothelial NO production (9). A transient increase in Ca 2ϩ also can trigger other signaling pathways that influence microvascular permeability (8,13).…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, a pressure increase can stimulate stretch-activated cation channels and induce Ca 2ϩ influx that induces endothelial NO production (9). A transient increase in Ca 2ϩ also can trigger other signaling pathways that influence microvascular permeability (8,13).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, ␤ 1 -integrins are associated with caveolae within which caveolin and signaling complexes regulate the activity of endothelial NO synthase (15,25,35,38). Direct or indirect activation of ion channel activity has also been implicated as an endothelial mechanosensor (1,3,8,16,18,19,43). Taken together, myriad signaling pathways could account for the observed DVR endothelial response to luminal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of endothelial cells by hemodynamic forces leads to an increase in [Ca 2/ ] i (7)(8)(9), presumably via the release from intracellular stores and Ca 2/ influx into the cell. Ca 2/ influx involves Ca 2/ -permeable, mechanosensitive ion channels (7,(10)(11)(12)(13), but the regulation of intracellular Ca 2/ release under mechanical stimulation by hemodynamic forces is incompletely understood. Recently, it has been demonstrated that shear stress induces oscillatory increases in [Ca 2/ ] i (14).…”
mentioning
confidence: 99%